Pengembangan Media Pembelajaran Berbasis Articulate Storyline 3 pada Pembelajaran Pendidikan Pancasila Kelas V SD di Gugus II Kec. Nanggalo Padang - Azizah, Hidayatul; Mansurdin, Mansurdin (YASIN, 2025)
Technological advancements in education require teachers to develop engaging and interactive digital learning media to enhance students’ learning motivation. However, in practice, many teachers still rely on textbooks, worksheets, and basic visual aids, resulting in monotonous and less innovative learning experiences. This study aims to develop a learning medium based on Articulate Storyline 3 for the Pancasila Education subject for fifth-grade students in Cluster II, Nanggalo District, Padang City, that is valid, practical, and effective. The method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 28 fifth-grade students from SDN 08 Surau Gadang and 22 fifth-grade students from SDN 09 Surau Gadang. Research instruments included validation sheets, practicality questionnaires, and effectiveness tests, analyzed through validity, practicality, and effectiveness assessments. The results show that the developed learning media achieved a validity score of 86% (categorized as very valid), a practicality score of 93.75% from teachers and 92.18% from students at SDN 08, and 96.87% from teachers and 96.44% from students at SDN 09 (categorized as very practical). The media also proved effective, as indicated by improved student learning outcomes at both schools. Thus, learning media based on Articulate Storyline 3 is deemed feasible and can serve as an innovative alternative for Pancasila Education instruction in elementary schools.